The effect of different materials under the fencing piste on impact shock of the tibia during the fencing lunge on a concrete surface - Holmes, K.; Sinclair, J.; Titan, A.; Holland, C.; Grebla, M.; Bottoms, L. (PLOS ONE, 2025)
Fencing has gained global popularity, with athletes often competing on hard surfaces, especially at United States national tournaments in convention centre with concrete floors. These surfaces may contribute to overuse injuries from high-impact movements like the fencing lunge. This study aimed to investigate tibial accelerations, a measure of impact shock, experienced by fencers during lunges on various surface materials placed beneath standard aluminium fencing pistes. The aim was to identify a material that could reduce injury risk by mitigating impact shock. Sixty-nine fencers (35 female) performed five lunges on six different surfaces (A-F: A-E composed of various materials placed between the aluminium piste and the concrete floor; F was only the concrete floor), during the 2024 US Senior National Championships. A triaxial accelerometer mounted on the tibia was used to measure tibial accelerations as a marker of impact shock. The accelerometer was aligned to measure acceleration along the longitudinal axis of the tibia and set to record at 1000 Hz with a sensitivity range of ± 100 g. Data acquisition was carried out via a logging system (Biometrics DL1001, Gwent, UK), which was attached to the participant using a tightly fitted backpack. The peak positive axial tibial acceleration was extracted for each lunge and the average was calculated from three lunges after discarding the highest and lowest values from each surface. Statistical analysis revealed that Surface E (a non-absorbent vinyl loop material; 12.7 ± 7.6g), significantly reduced tibial accelerations compared to the standard concrete setup (Surface F; 13.6 ± 8.4g). These findings suggest that modifying competition surfaces by incorporating cushioning materials may help reduce the impact shock of the fencing lunge, potentially lowering the risk of overuse injuries, such as tendonitis and tenosynovitis, commonly reported by fencers. Future research should investigate optimal material properties, including thickness and softness, for maximizing injury prevention while maintaining performance standards in competitive fencing environments.